2020
DOI: 10.3390/cancers12040937
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma: Pathogenesis and Current Status of Chemotherapy and Other Novel Treatments

Abstract: Glioblastoma is one of the most common and detrimental forms of solid brain tumor, with over 10,000 new cases reported every year in the United States. Despite aggressive multimodal treatment approaches, the overall survival period is reported to be less than 15 months after diagnosis. A widely used approach for the treatment of glioblastoma is surgical removal of the tumor, followed by radiotherapy and chemotherapy. While there are several drugs available that are approved by the Food and Drug Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 161 publications
(129 reference statements)
0
96
0
Order By: Relevance
“…GBM has a global incidence of 10 per 100,000 of the population and can affect people of all ages, although peak age of diagnosis falls between 45 and 75 years [ 6 ]. Primary GBM (those that arise de novo) account for 95% of tumours, whereas those arising from precursor less malignant gliomas (secondary, usually with an IDH mutation) account for the remaining 5% [ 7 ]. Treatment prospects are bleak for GBM; initial surgical intervention is the main predictor of outcome and is necessary to gain a clear histological diagnosis for the glioma.…”
Section: Gliomamentioning
confidence: 99%
“…GBM has a global incidence of 10 per 100,000 of the population and can affect people of all ages, although peak age of diagnosis falls between 45 and 75 years [ 6 ]. Primary GBM (those that arise de novo) account for 95% of tumours, whereas those arising from precursor less malignant gliomas (secondary, usually with an IDH mutation) account for the remaining 5% [ 7 ]. Treatment prospects are bleak for GBM; initial surgical intervention is the main predictor of outcome and is necessary to gain a clear histological diagnosis for the glioma.…”
Section: Gliomamentioning
confidence: 99%
“…This combination of treatment has demonstrated a 2-month increase in life expectancy from 12.2 to 14.6 months, and a 16% increase in 2-year survival (Stupp et al 2009). Over the past decade, many drugs have entered clinical trials for treatment of gliomas including epidermal growth factor receptor (EGFR) targeted therapies (Rajaratnam et al 2020), protein kinase B (Akt) inhibitors (Kaley et al 2019;Wen et al 2013), mutant isocitrate dehydrogenase (IDH1) inhibitors (Fan et al 2020) and calcium channel inhibitors (Holdhoff et al 2017). Despite intense research efforts, minimal changes to GBM patient life expectancy have been observed since the introduction of TMZ therapy over 10 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…G lioblastoma is the most common malignant primary brain tumor and is the focus of extensive basic and clinical research efforts targeting improved therapies. 1,2 Technologies related to the establishment of primary low passage tumor cultures are increasingly important to oncology research and practice. [3][4][5][6][7] However, processing of fresh tumor specimens for the establishment of primary cultures on the day of surgical collection is logistically difficult.…”
Section: Introductionmentioning
confidence: 99%